Mathematical Uncertainty Relations and their Generalization for Multiple Incompatible Observables - Nguyen, Hung Quang; Bui, Tu Quang (VNU Journal of Science: Mathematics - Physics; Vol 33 No 1DO - 10.25073/2588-1124/vnumap.4075, 2017)
We show that the famous Heisenberg uncertainty relation for two incompatible observables can be generalized elegantly to the determinant form for N arbitrary observables. To achieve this purpose, we propose a generalization of the Cauchy-Schwarz inequality for two sets of vectors. Simple consequences of the N -ary uncertainty relation are also discussed. Keywords: Generalized uncertainty relation, Generalized uncertainty principle, Generalized Cauchy-Schwarz inequality.